Persistent omphalomesenteric duct: a rare cause of acute intestinal volvulus in an adolescent treated by laparoscopy - Gomes, Maria Miguel (2019)
This report describes the case of a 14-year-old male with a prior history of recurrent abdominal pain and two previous ”sub-occlusive” episodes. He presented at the Emergency Room with abdominal pain, emesis, abdominal distension, painful palpation, and signs of peritoneal irritation. Plain upright abdominal radiography suggested a distal small bowel obstruction. Exploratory laparoscopy showed a tubular structure connecting the antimesenteric border of the terminal ileum and the umbilicus, which was behaving as a rotation axis to the small intestine. The volvulus was laparoscopically de-rotated, and the structure was excised. Histological exam confirmed the diagnosis of persistent omphalomesenteric duct. This case illustrates an intestinal obstruction caused by small intestine volvulus. A high index of suspicion is required to acknowledge this etiology.